A conceptual model for feedback control based instruction and evaluation. (23rd March 2009) - Lohani, Vinod K.; Kachroo, Pushkin
This paper presents a framework for formative or feedback control based system for engineering instruction and evaluation. The system involves formal knowledge representation using appropriate data structures that are XML compliant. A metric topology is used on the data structure which then can be used to develop quantitative measures of learning effectiveness and also for quantifying knowledge-error needed for feedback learning loop.